Global burden of cardiovascular diseases attributable to diet low in seafood omega-3 fatty acids from 1990~2021 and forecasting the future trends: A population-based study - Qingsong Mao; Xinling Tian; Xingyi Wang; Haitao Xu; Yunyi Zhang; Yuzhe Kong (PLoS ONE, 2025)
Background This research investigates the worldwide influence of cardiovascular diseases (CVD) associated with low intake of seafood omega-3 fatty acids, based on data from the 2021 Global Burden of Disease Study. Method The study evaluated the effects of insufficient seafood omega-3 fatty acid consumption on CVD at international, regional, and country levels. It analyzed variations across different demographics, including age and gender, and explored the relationship between disease burden and the Socio-Demographic Index (SDI). Additionally, it utilized an ARIMA model to predict the incidence of CVD connected to this dietary deficiency until 2050. Result In 2021, diets deficient in seafood omega-3 fatty acids contributed to roughly 737.88 thousand deaths and 17.87 million disability-adjusted life years (DALYs) from CVD, with a noted decrease in this health impact over the period studied. The most substantial effects were seen in the elderly, particularly those aged 75 and above, with males experiencing a higher disease impact. Future forecasts suggest probable declines in disease rates across all SDI areas. However, nations in North Africa and the Middle East are projected to encounter growing difficulties related to CVD stemming from low seafood omega-3 intake by 2030 and 2050. Conclusion These results highlight the critical need for preventive strategies against CVD and stress the significance of dietary management.